Sertifikat Pendidik Syarat Mutlak Dalam Pengangkatan Jabatan Fungsional Guru Dan Peningkatan Kesejahteraan Guru - Jaya Saputra, Deni (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2022)
Teachers as the foundation for the creation of quality education must always develop their abilities and professionalism.  Educator certificates are awarded to teachers who have met teacher professional standards.  In the Minister of Education and Culture Regulation Number 38 of 2020 concerning Procedures for Obtaining Educator Certificates for Teachers in Internal Positions, it is regulated that educator certificates for in-service teachers are carried out through the in-service PPG program.  To get a certificate, you must pass PPG which is carried out for 6 months.  With the mechanism, the teacher must register as a prospective student for the PPG program by following the administrative selection, attending lectures of 36 credits, comprehensive testing, PPL, competency test for teacher professional education students.  After passing the teacher professional education competency test, then PPG program students are given an educator certificate by the educational staff education institution.  The procedures and mechanisms for obtaining certificates are numerous and lengthy processes.  Because of this, the implementation of madrasah teacher certification in Riau Province in 2020 is PNS teachers who do not have a certificate of 10.81%, totaling 236 teachers, while non-PNS teachers who do not have a certificate are 53.27% totaling 8,809 teachers.  This condition, if allowed to continue, will add to the long queues for novice teachers to obtain certificates which are a requirement for appointment to functional teacher positions